Dampak Implementasi Kebijakan Renewable Energy Directive II terhadap Hubungan Indonesia - Uni Eropa - Bukkang, Yun Silva; Bt. Mamma, Beche; Burhan, Zulkhair (Universitas Bosowa, 2023)
This research will write down the impact of implementing the Renewable Energy Directive II policy issued by the European Union to regulate the use of renewable energy as a form of the European Union's commitment to Sustainable Development Goals (SDGs). In the Renewable Energy Directive II Policy issued by the European Union, it is stated that palm oil causes deforestation or environmental damage. Indonesia, which has long established economic cooperation with the European Union, especially in the export-import of palm oil, as the world's largest producer of palm oil, feels discriminated against the policy issued. Indonesia gets the country's largest foreign exchange from exports of palm oil and its derivatives which will then have a major impact on the decline in imports of palm oil by the European Union after the issuance of this policy. This research question is